CANGGET SEBAGAI IDENTITAS KULTURAL PADA MASYARAKAT LAMPUNG - Martiara, Rina (Acintya, 2009)
This article talking about a Cangget dance of Lampung society and its identity related to the dance performance itself The Cangget dance and its specific field of its performance because of it was danced by a group of female dancers. Uniquelly the female dancers mostly the daughters of the traditional ethnic leaderand their appearance represents the unappearance of the ethnic leaders. Here! would like to examine through this article in what kind of the Cangget dance and its role as a culktural identity amongs Lampung society furthe rmore the extended role of this dance tradition presently. In other ways this article will also examine the Cangget dance by using sosio-historical approach in order to analyze the Cangget dance and its existence into the pattern of culture, system of value and its norms related to the intercontextualities of cultural diversity.Â Keywords: Cangget dance, cultural identity, society.